Psychology Analysis of Main Character in the Novel Gitanjali by Febrialdi R - Zilfa A. Bagtayan; Jafar Lantowa (Pioneer: Journal of Language and Literature, 2022)
This study aims to describe the psychology of main characters in the novel Gitanjali by Febrialdi R. In detail, the purpose of this study is to describe the psyche of the main character when facing various kinds of problems in his life. This research uses the library method. The subject of this research is a novel entitled Gitanjali by Febrialdi R which was published by mediakita publisher in 2018. This study focuses on problems related to the psychological conflict experienced by the main character. The results showed that: First, the main character of the novel Gitanjali received injustice. An accident that happened when he worked at a restaurant made him dismissed from the restaurant because of his disability. Second, the main character experiences despair in his life and love relationship. He feels hopeless about his love relationship which is not going well due to the demanding parents of his partner. It made him insecure, moreover his partner was a lecturer while he was just an ordinary man. Third, the main character lives alone because since childhood he never knew his biological parents and only lived in an orphanage. Fourth, the main character is depressed due to the problems that come his way.